Knockdown Resistance-Associated Mutations Dominate Populations of the Common Bed Bug (Hemiptera: Cimicidae) Across the South Central United States. Issue 6 (27th June 2019) - Holleman, Jeffrey G; Robison, Grant A; Bellovich, Ian J; Booth, Warren
Abstract: Despite awareness of the mutations conferring insecticide resistance in the bed bug, Cimex lectularius L. (Hemiptera: Cimicidae), within the United States few studies address the distribution and frequency of these. Within the United States, studies have focused on collections made along the East Coast and Midwest, documenting the occurrence of two mutations (V419L and L925I) within the voltage-gated sodium channel α-subunit gene shown to be associated with knockdown resistance ( kdr ) to pyrethroids. Here, the distribution and frequency of the V419L and L925I site variants is reported from infestations sampled within Oklahoma and its immediately adjacent states. Additionally, the presence of a mutation previously undocumented in the United States (I935F) is noted. While novel in the United States, this mutation has previously been reported in Australian and Old World populations. No infestations were found to harbor wild-type individuals, and hence susceptible, at each of the three sites. Instead, 21% were found to possess the resistant mutation at the L925I site (haplotype B), 77% had mutations at both the V419L and L925I sites (haplotype C), and 2% possessed the mutation at the L936F site (haplotype A b ). The high frequency of haplotype C corresponds to previous studies in the United States, and contrasts dramatically with those of the Old World and Australia. The data presented here provide insight into the contemporary occurrence of kdr- associated insecticide resistance in the South Central United States, a region for which data have previously been absent. These data suggest that New World and Old World/Australian infestations are likely to have originated from different origins.